2015
DOI: 10.1121/1.4928954
|View full text |Cite
|
Sign up to set email alerts
|

Memory disruption by irrelevant noise-vocoded speech: Effects of native language and the number of frequency bands

Abstract: To investigate the mechanisms by which unattended speech impairs short-term memory performance, speech samples were systematically degraded by means of a noise vocoder. For experiment 1, recordings of German and Japanese sentences were passed through a filter bank dividing the spectrum between 50 and 7000 Hz into 20 critical-band channels or combinations of those, yielding 20, 4, 2, or just 1 channel(s) of noise-vocoded speech. Listening tests conducted with native speakers of both languages showed a monotonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
56
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 28 publications
14
56
3
Order By: Relevance
“…This is in agreement with one previous study by Ellermeier et al (2015), which also used noise-vocoded speech in an irrelevant-speech task. Going beyond noise-vocoding, several studies using other auditory signal processing techniques have demonstrated higher distraction by acoustically more intact task-irrelevant speech (e.g., Tremblay et al, 2000; Little et al, 2010; Viswanathan et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with one previous study by Ellermeier et al (2015), which also used noise-vocoded speech in an irrelevant-speech task. Going beyond noise-vocoding, several studies using other auditory signal processing techniques have demonstrated higher distraction by acoustically more intact task-irrelevant speech (e.g., Tremblay et al, 2000; Little et al, 2010; Viswanathan et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The crossings of these factor-loading curves separated four frequency bands that were similar across these languages/dialects. These four bands were used by our research group to generate noise-vocoded speech in Japanese and German when the present analysis was on the way, and the generated signals indicated high intelligibility of up to 95%3. These results were consistent with representative past data on noise-vocoded speech45.…”
supporting
confidence: 84%
“…However, evidence from ERP (Berti and Schroger, 2003; Muller-Gass and Schroger, 2007) and behavioral (Dalton et al, 2009) studies that utilized purely auditory paradigms supports an alternative view that distracter suppression occurs at a later stage and requires active control (Berti and Schroger, 2003; Dalton et al, 2009). At the same time, recent behavioral studies also suggest that during auditory WM, irrelevant speech sounds are suppressed only after initial feature processing (Ellermeier et al, 2015; Wöstmann and Obleser, 2016). The present results seem to be more consistent with the latter group of ERP and behavioral studies: The aspect of left AC time course that was statistically significantly modulated by the contextual WM maintenance load was relatively late, clearly after the P50/N1/P2 pattern that is thought to reflect the emergence of conscious sound percept and the initiation of stimulus encoding in ACs (Parasuraman and Beatty, 1980).…”
Section: Discussionmentioning
confidence: 96%